On conformal points of area preserving maps and related topics - Albers, Peter; Tabachnikov, Serge (Journal of geometry and physics, 2022)
In this article we consider area preserving diffeomorphisms of planar domains, and we are interested in their conformal points, i.e., points at which the derivative is a similarity. We present some conditions that guarantee existence of conformal points for the infinitesimal problem of Hamiltonian vector fields as well as for what we call moderate symplectomorphisms of simply connected domains. We also link this problem to the Carathéodory and Loewner conjectures.
Online veröffentlicht am 8 August 2022, Artikelversion 17 August 2022
Gesehen am 09.12.2022